Malting Quality of Winter Wheat (Triticum aestivum L.) - Psota, Vratislav; Musilová, Markéta; Sachambula, Lenka; Horáková, Vladimíra; Přinosil, Aleš; Šmíd, František; Adámková, Karolína; Adam, Martin (My University, 2018)
In the course of three testing years (2013 – 2015), a set of 243 winter wheat samples (27 varieties from three testing sites) were analyzed. Basic technological parameters, and some special characters (wort color, color after boiling, wort haze, polyphenol content and dimethyl sulfide precursors) were studied. Winter wheat varieties gave sufficiently high extract contents, the average value of this parameter was 83.5% at the average content of nitrogenous substances of 11.6%. Final attenuation was low (79.8%). Proteolytic modification given by the value of Kolbach index was on average 35%. Content of soluble nitrogen was 704 mg/100 g, of which ca 14% was made up by free amino nitrogen. Cytolytic modification was evaluated mainly by wort viscosity (1.864 mPa.s). Malt friability and β-glucan content in wort were very low. Average arabinoxilan content in wort varied about 1524 mg/l.
Sladovnická kvalita odrůd ozimé pšenice (Triticum aestivum L.)
Keywords: Winter wheat; Malting quality; Ozimá pšenice; Sladovnická kvalita